OP0218 Investigating the regulatory snps at the runx3 locus associated with ankylosing spondylitis. (12th June 2018) - Vecellio, M.L.; Cortes, A.; Cohen, C.J.; Fischer, R.; Wordsworth, B.P.
Abstract : Background: Among the 100 genes associated with ankylosing spondylitis (AS), RUNX3 a transcription factor (TF) involved in diverse immunological processes has a very robust (10 −15 ) association. 1 The biggest challenge following association studies remain to understand the mechanism behind this association and get insights of the disease. We have recently demonstrated that the association between AS and the single nucleotide polymorphism (SNP) rs4648889 located in a 2 kb regulatory locus upstream the promoter of RUNX3 can be explained by allele-specific effects on TF recruitment that alter gene expression, specifically in CD8 +T cells. 2 In addition, another closely adjacent SNP, rs4265380 shows functional effects (i.e. TF recruitment, histone marks enrichment and cell count) on CD14 +monocytes. 3 Objectives: The main objectives of this work are: 1) to dissect the functional effects of the different SNPs at the RUNX3 locus, acting in different cell types (especially CD8 +T cells and monocytes); 2) to identify the different interacting partners (i.e. TFs) binding at the RUNX3 locus in the presence of the AS-associated alleles. Methods: We used publicly available dataset to define the epigenetic landscape of the RUNX3 locus. In vitro functional studies were performed to characterise the effects of these specific genetic variants, providing critical functional evidence for their role in AS. Results: (1) Roadmap data revealed a robust peak for open chromatin and specific histone modifications associated with regulatory elements. Hi-C data showed the interaction of RUNX3 with different genomic loci within chromosome 1, in GM12878 lymphoblastoid cell line, CD8 +T cells and monocytes; (2) ChIP-qPCR experiments on monocytes and CD8 +T cells from AS patients revealed the enrichment for several histone modifications (i.e. H3K79Me2 and H3K4Me1) at the RUNX3 locus overlapping the SNPs of interest; (3) preliminary DNA pull-down experiments, followed by Mass Spectrometry, started to identify the whole range of proteins and TFs (DNA/protein 'interactome') that bind at the RUNX3 locus in the presence of the AS-associated alleles, evaluated in both CD8 +T cells and monocytes; (4) initial pathway enrichment analysis highlighted the distinct contribution of proteins involved in the transcriptional machinery (AS-risk VS protective alleles). Conclusions: We provide first evidence that the 2 kb region upstream the RUNX3 gene has a plausible functional role in AS. These new observations are critically important not only in identifying specific cell types that play a pathogenic role in AS, but also in defining dysregulated pathways and potential therapeutic drug targets. References: [1] ] IGAS, et al. Nat Genet2013Jul;45(7):730–8. [2] Vecellio M, et al. Ann Rheum Dis2016Aug;75(8):1534–40. [3] Vecellio M, et al. RMD Open 2018. Disclosure of Interest: None declared